Psychometric properties of the proxy-reported Life-Space Assessment for Institutionalized Settings (LSA-IS-Proxy) for older persons with and without cognitive impairment - Hauer, Klaus; Ullrich, Phoebe; Heldmann, Patrick; Bauknecht, Laura; Hummel, Saskia; Abel, Bastian; Bauer, Jürgen M.; Lamb, Sarah E.; Werner, Christian (International journal of environmental research and public health, 2021)
(1) Background: Life-space mobility assessments for institutionalized settings are scarce and there is a lack of comprehensive validation and focus on persons with cognitive impairment (CI). This study aims to evaluate the psychometric properties of the Life-Space Assessment for Institutionalized Settings by proxy informants (LSA-IS-proxy) for institutionalized, older persons, with and without CI. (2) Methods: Concurrent validity against the self-reported version of the LSA-IS, construct validity with established construct variables, test-retest reliability, sensitivity to change during early multidisciplinary geriatric rehabilitation treatment, and feasibility (completion rate, floor/ceiling effects) of the LSA-IS-proxy, were assessed in 94 hospitalized geriatric patients (83.3 ± 6.1 years), with and without CI. (3) Results: The LSA-IS-proxy total score showed good-to-excellent agreement with the self-reported LSA-IS (Intraclass Correlations Coefficient, ICC3,1 = 0.77), predominantly expected small-to-high correlations with construct variables (r = 0.21-0.59), good test-retest reliability (ICC3,1 = 0.74), significant sensitivity to change over the treatment period (18.5 ± 7.9 days; p < 0.001, standardized response mean = 0.44), and excellent completion rates (100%) with no floor/ceiling effects. These results were predominantly confirmed for the sub-scores of the LSA-IS-proxy and were comparable between the sub-groups with different cognitive status. (4) Conclusions: The LSA-IS-proxy has proven to be feasible, valid, reliable, and sensitive to change in hospitalized, geriatric patients with and without CI.